Transferring Irrigation Management to Farmer's Associations : Evidence from the Philippines - Bandyopadhyay, S.; Shyamsundar, P.; Xie, M. (2012)
Irrigation management transfer (HAT) is an important strategy among donors and governments that aims to strengthen farmer control over water and irrigation infrastructure. In this study. we use data from a survey of 68 irrigator associations (IAs) and 1020 farm households in the Philippines to examine the impact of IMT on irrigation association performance and on rice yields We find that the presence of IMT is associated with an increase in maintenance activities undertaken by irrigation associations While associations with and without IMT contracts undertake canal maintenance. the frequency of maintenance in IMT IAs is higher IMT presence is also associated with an increase in farm yields by about 6%, rice production in IMT areas is higher even after we control for various differences amongst rice farmers in IMT and non-IMT areas Finally. IMT may even give poorer farmers a small boost in terms of rice yields We speculate that this boost may be a result of improved water delivery and better resolution of conflicts related to illegal use.